2014
DOI: 10.3748/wjg.v20.i29.10071
|View full text |Cite
|
Sign up to set email alerts
|

KISS1methylation and expression as predictors of disease progression in colorectal cancer patients

Abstract: These data suggest that KISS1 is down-regulated in cancer tissues via promoter hypermethylation and therefore may represent a candidate target for treating metastatic CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…14 Moreover, Chen et al declared that there is hypermethylation of this gene in 83.33% of primary CRC vs. 6.30% in normal intestine specimens and also there is an association with the depth of local invasion, tumor differentiation and tumor metastatic features. 15 In contrast, it is interesting that the present study using MS-HRM assay discovered no statistically significant differences between 3 0 flanking region methylation of tumor samples and adjacent tumor-free samples for KISS1; Table 3. The correlations of cilinicopathological characteristics of EDNRB and KISS1 gene methylation status.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…14 Moreover, Chen et al declared that there is hypermethylation of this gene in 83.33% of primary CRC vs. 6.30% in normal intestine specimens and also there is an association with the depth of local invasion, tumor differentiation and tumor metastatic features. 15 In contrast, it is interesting that the present study using MS-HRM assay discovered no statistically significant differences between 3 0 flanking region methylation of tumor samples and adjacent tumor-free samples for KISS1; Table 3. The correlations of cilinicopathological characteristics of EDNRB and KISS1 gene methylation status.…”
Section: Discussioncontrasting
confidence: 39%
“…30,31 It has been reported that EDNRB and KISS1 as the tumor suppressor and tumor metastasis suppressor genes, respectively, are silenced in various cancers such as colorectal cancer, which is caused by specific CpG islands' hypermethylation. [13][14][15] Regarding EDNRB, which encodes a G-protein coupled receptor, it is implicated that hypermethylation of CpG dinucleotides in 5 0 flanking region happens during CRC progression. 13 Indeed, this aberrant methylation is associated with the EDNRB downregulation and silencing that may be involved in the cell proliferation, 14,15 In the present study, EDNRB hypermethylation in CRC confirmed quantitatively for the first time by MS-HRM assay, concordant with what previously found in Chen et al study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations